Experimental Study on Creep Characteristics of Saturated Q2 Loess - Xiaowei Liu; Xiaowei Liu; Xudong Zhang; Xiaogang Fu; Tianxiang Yang; Zisong Su (Frontiers in Earth Science, 2022)
Catastrophic failures often occur to engineered infrastructure in areas underlain by saturated loess due to its high moisture content (degree of saturation >85%), low shear strength, and large deformation. Time effect (rheological property) and water are the most important factors affecting the mechanical properties of saturated loess. The rheological mechanism and characteristics of saturated loess are vital to understanding the interaction between infrastructure and foundation and the trigger of failures. Based on step-load testing, this study obtains the displacement-time relationship of saturated Q2 loess to analyze its creep behavior. Experimental results show that the creep strength of saturated Q2 loess is 75–80% of its unconfined compression strength, and the creep behavior can be simulated by the Burgers model. Additionally, the rheological parameters under different load conditions are obtained using the improved Marquardt iterative method. All these parameters can be used for numerical analysis of the rheological behavior of saturated Q2 loess.